Origami-based spintronics in graphene - FERREIRA, MAURO (My University, 2013)
We show that periodically folded graphene sheets with enhanced spin-orbit interaction due to curvature effects can carry spin-polarized currents and have gaps in the electronic spectrum in the presence of weak magnetic fields. Our results indicate that such origami-like structures can be used efficiently in spintronic applications.
PUBLISHED
Keywords: graphene; Nanoscience & Materials